PEMBERDAYAAN POKDARWIS KAMPUNG EMBUNG WONOLOPO KOTA SEMARANG BERBASIS KEARIFAN LOKAL MENDUKUNG KAWASAN WISATA - dwi, Dwi Prastiyo Hadi; Riyanto, Riyanto; Sutrisno, Sutrisno (Universitas Mataram, 2024)
Wonolopo Tourism Village is a Thematic Village that supports tourism packages, with the presence of a reservoir, Wonolopo Village has more visitors, for that reason souvenirs are needed that are typical of Wonolopo Village, Wonolopo Village has agricultural potential in the form of cassava, sweet potatoes, bananas, aloe vera. In order to be more optimal, it will be processed into products that are typical of Wonolopo Village and can improve the community's economy. The purpose of this activity is to find solutions to the problems of the Wonolopo Village community with a community empowerment approach, so as to strengthen the community's potential and form a tourist village